1996
DOI: 10.2170/jjphysiol.46.481
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Light Intensities during the Daytime on the Forearm Blood Flow and Mean Body Temperature in the Evening.

Abstract: The subjects were exposed to bright or dim light during the daytime. Compared to dim light exposure, bright light exposure induced a steeper slope in the regression line between the skin blood flow of the forearm and mean body temperature under an external heat load in the evening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It might have been due to a reduced set-point of core temperature induced by the exposure to 6-h bright light during the morning. A reduced set-point of core temperature under the in¯uence of the bright light has previously been suggested for thermal sensation (Teramoto et al 1996), for rectal (Tokura et al 1994) and tympanic (Aizawa and Tokura 1997) temperatures, for dressing behaviour in the cold (Kim and Tokura 1995) and for the relationship between forearm skin blood¯ow and mean body temperature (Aizawa and Tokura 1996). The reduced set-point of core temperature might have acted to inhibit the increase of rectal temperature via an increase of melatonin concentration (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…It might have been due to a reduced set-point of core temperature induced by the exposure to 6-h bright light during the morning. A reduced set-point of core temperature under the in¯uence of the bright light has previously been suggested for thermal sensation (Teramoto et al 1996), for rectal (Tokura et al 1994) and tympanic (Aizawa and Tokura 1997) temperatures, for dressing behaviour in the cold (Kim and Tokura 1995) and for the relationship between forearm skin blood¯ow and mean body temperature (Aizawa and Tokura 1996). The reduced set-point of core temperature might have acted to inhibit the increase of rectal temperature via an increase of melatonin concentration (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, we have found that exposure to bright light of 4000 lux from 0930 hours to 1800 hours induced a steeper slope of the regression line between skin blood ow of the forearm and mean body temperature under an external heat load in the evening than after dim light of 100 lux (Aizawa and Tokura 1996). Although all these ®ndings would suggest that bright light exposure during the daytime may modulate thermoregulation in humans and probably reduce the set point of core temperature, it seems necessary that more data be collected under various conditions to draw these conclusions.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, the effect of bright light exposure on subsequent sleep appears to depend on the effect on body temperature: A stronger decrease is associated with sleep facilitation, whereas an attenuated decrease is associated with a longer sleep latency. It has indeed been shown that bright light exposure during the day causes a stronger release of peripheral vasoconstrictor activity during the subsequent night, resulting in increased skin blood flow and skin temperature and decreased rectal temperature (Aizawa and Tokura 1996). It should be noted that bright light not only temporarily affects temperature, but also can increase the general level of arousal (Badia et al 1991) as well as shift the circadian rhythm and thereby either improve (Campbell et al 1993) or disturb (Cajochen et al 1992) sleep.…”
Section: Effects On Sleep Of Changes In Thermoregulation and Body Andmentioning
confidence: 99%